2021
DOI: 10.1590/1516-3180.2020.0722.r1.2302021
|View full text |Cite|
|
Sign up to set email alerts
|

Could serum total cortisol level at admission predict mortality due to coronavirus disease 2019 in the intensive care unit? A prospective study

Abstract: BACKGROUND: Critical diseases usually cause hypercortisolemia via activation of the hypothalamic-pituitary-adrenal axis. OBJECTIVES: To investigate the relationship between serum total cortisol level and mortality among coronavirus disease 2019 (COVID-19) patients in the intensive care unit (ICU), at the time of their admission. DESIGN AND SETTING: Prospective study developed in a pandemic hospital in the city of Şırnak, Turkey. METHODS: We compared the serum total cortisol levels of 285 patients (141 COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
(31 reference statements)
3
27
0
2
Order By: Relevance
“…The majority of critical patients in the ICU included in our study were male with the median age of 74 years. This finding was similar to the studies in the literature [24][25][26][27]. Among the comorbid diseases, only cardiovascular diseases were found to be significantly higher in the nonsurvivor group.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of critical patients in the ICU included in our study were male with the median age of 74 years. This finding was similar to the studies in the literature [24][25][26][27]. Among the comorbid diseases, only cardiovascular diseases were found to be significantly higher in the nonsurvivor group.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the higher the cortisol levels, the greater was the hazard of mortality, in consistence with numerous previous studies in non-COVID-19 patients, suggesting that cortisol is a marker of disease severity. In critically ill patients, the results were similar; in a study of 144 COVID-19 critically ill patients, high levels of cortisol were observed in the patients with more severe illness and reduced survival [ 42 ]. A positive association with disease severity was also confirmed in the study by Das et al, who reported higher cortisol levels in COVID-19 patients with moderate to severe disease compared to those with mild disease [ 43 ].…”
Section: Pituitary–adrenal Responses In Covid-19 Patientsmentioning
confidence: 82%
“…If further research can validate or extend our ndings then certainly such small, engineered animal models could serve as important tools in ghting, and winning this non-stop COVID-19 pandemic, and other related infectious diseases. As shown by others that a heightened pathological response in the form of increased cytokine storm and multi-organ damage can lead to vital organ failure, and ultimately death in some COVID-19 patients as already revealed during the last ~2 years since the start of the pandemic [70][71][72][73][74][75][76][77][78][79][80][81][82]. To dissect out further the physiological and pathological implications of the SARS-CoV-2 induced changes, we set out this important study to captures some of the initial/beginning phase of the intimate interaction(s) between the host cell receptor with the SARS-CoV-2 spike (S) protein employing a humanized/genetically engineered mouse model expressing the human angiotensin converting enzyme 2 (hACE2) and the recombinant SARS-CoV-2 spike (S) that was delivered via the intranasal route [83].…”
Section: Discussionmentioning
confidence: 99%